The development and validation of a tablet-based assessment battery of general cognitive ability - Dong-ni Pan; Hailun Xie; Yanjia Zeng; Yixiang Zhou; Cuizhu Lin; Xin Ma; Juejing Ren; Yuanyun Jiao; Yingying Wu; Wei Wei; Gui Xue (BMC Psychology)
Abstract Background Traditional cognitive assessments, often reliant on paper-and-pencil tests and professional evaluators, suffer from subjectivity and limited result discrimination. This study introduces the Baguan Online Cognitive Assessment System (BOCAS), a tablet-based system that evaluates both general cognitive ability (GCA) and domain-specific functions across six domains: sensory-motor skills, processing speed, sustained attention, working memory, cognitive flexibility, and spatial ability. Methods BOCAS was validated with 151 healthy Chinese adults aged 18–40. Reliability was assessed through internal consistency and test-retest reliability. Factor analysis and confirmatory factor analysis (CFA) were used to validate the model. The GCA score was correlated with the Raven IQ test and self-reported cognitive flexibility, and its relationship with negative emotions (depression and anxiety) was examined. Results BOCAS showed satisfactory reliability, with internal consistency ranging from 0.712 to 0.846 and test-retest reliability from 0.56 to 0.71. Factor analysis revealed a common factor explaining 40% of the variance, and CFA indicated a good model fit (χ²/df = 1.81; CFI = 0.932). The GCA score strongly correlated with the Raven IQ test (r = 0.58) and was related to self-reported cognitive flexibility and negative emotions. Conclusion BOCAS offers a digital solution for cognitive assessment, providing automated, remote, and precise evaluations. It demonstrates reliability, validity, and potential for use in clinical and research settings.